A Case of Arteriovenous Malformation Located in Retroperitoneum - Wang, Cong (Hinyokika kiyo. Acta urologica Japonica, 2016)
A 67-year-old woman was referred to our hospital for precise examination and treatment as an abdominal computed tomographic (CT) scan showed a retroperitoneal tumor located below the hilus of the right kidney. The enhanced CT and magnetic resonance imaging (MRI) revealed contrast enhancement in both early and late phase, which confirmed that the tumor showed abundant blood perfusion and adhered to the duodenum. We performed open surgery in order to remove the tumor and make a precise diagnosis. The tumor was excised en bloc with a part of the gonadal vein because the right gonadal vein was adjacent to the tumor in the craniocaudal direction. The pathological diagnosis was arteriovenous malformation. Arteriovenous malformation located in the retroperitoneum is very rare